FAKTOR-FAKTOR YANG MEMENGARUHI PENYERAPAN TENAGA KERJA IBS PROVINSI JAWA TIMUR TAHUN 2019 - Adinda Haya Shafira; Krismanti Tri Wahyuni (Politeknik Statistika STIS, 2020)
The success of a country's economic development is determined by its human resources, but a large population does not always guarantee the success of development, and can even become a burden for the sustainability of development if it cannot be utilized optimally. Apart from having a role as the main sector in economic development, the industrial sector also has the potential to absorb a large number of workers. However, the fact is that East Java Province has not been able to fulfill this, where the absorption of labor in the industrial sector is still behind compared to the agricultural and trade sectors even though the industrial sector is the leading sector and the largest contributor to GRDP of East Java Province. The purpose of this study is to identify, describe, and analyze the factors that affect the employment of large and medium industries in East Java Province in 2019. The method used is multiple linear regression analysis (RLB). The results of the analysis show that at least one independent variable has a significant effect on the absorption of labor in the large and medium industrial sector in East Java Province in 2019. Partially, the variable number of companies and GRDP has a significant and positive effect on employment in the large and medium industrial sector in East Java Province in 2019. 2019. Meanwhile, the UMK variable does not have a significant effect on the absorption of labor in the large and medium industrial sector in East Java Province in 2019, because the increase in wages is a burden for the company.